Re-emphasising the importance of histopathological diagnosis in suspected bacterial endocarditis. (January 2023) - Naderi, Hafiz; Abbara, Aula; Viviano, Alessandro; Asaria, Perviz; Pabari, Punam A; Flora, Rashpal; Punjabi, Prakash P; Rana, Bushra S
Infective endocarditis (IE) carries a high risk of morbidity and mortality. Timely diagnosis, effective treatment and prompt recognition of complications are essential to favourable patient outcomes. A collaborative, multidisciplinary team approach to the management of IE has been shown to improve prognosis. However, the clinical heterogeneity of IE and atypical presentations pose challenges to the endocarditis team. We present a case highlighting the role of valve histopathology in suspected IE, where there may be diagnostic uncertainty.